Motion Graphic-Based Digital Media Development for Stunting Education - Dadan Nugraha (SEA-CECCEP, 2022)
This research is oriented to the development of motion graphic-based digital media as learning media for stunting education. There are various types of digital media that can be used in learning. However, one of the digital media needed is learning videos. By using a research-based design or Design Based Research (DBR), a digital media is designed, namely learning videos based on needs analysis, development design, trial and evaluation. The results of expert validation, media validation and limited trials, digital media based on motion graphics are categorized as good, so the media designed is suitable for use as digital-based learning media for stunting education.